Well-posedness of generalized Kadomtsev–Petviashvili systems - Reyes-Garcia, E (World Scientific, 2025)
We review our results, published, prepublished or unpublished, on the well-posedness of selected generalized Kadomtsev–Petviashvili hierarchies. © 2025 World Scientific Publishing Company.